FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK (TAX AVOIDANCE) - Maria Melisa; Vivi Adeyani Tandean (Universitas Bunda Mulia, 2017)
Taxation is an important issue to sustain a country’s revenue. The main obstacle in the context of state income tax in this sector is tax avoidance. Minimizing of tax burden can be influenced by companies’ character and executive’s character. This study aims to examine the factors that affect tax avoidance. This study uses 205 manufacturing companies. Sample methods in this study is judgment sampling. This study’s hypothesis is tested with classical assumptions and multiple regression analysis using SPSS version 20 software. Conclusions for this research are company risk, leverage, and sales growth not have sufficient evidence to have impact on tax avoidance, size have sufficient evidence to have impact on tax avoidance.Keywords: tax avoidance, executive’s character, zise, leverage, and sales growth